ACOUSTIC ECHO CANCELLATION USING COMPUTATIONALLY EFFICIENT ADAPTIVE ALGORITHM TECHNIQUES - Shaik, Mastan Sharif; Prasad, K. Satya; Shaik, Rafi Ahamed; Rao, D. Venkata (APTIKOM Publisher, 2016)
Several sign based LMS adaptive filters, which are computationally free having multiplier free weight update loops, are proposed for acoustic echo cancellation. The adaptive filters essentially minimizes the mean- squared error between a primary input, which is the echo, and a reference input, which is either echo that is correlated in some way with the echo in the primary input. The results show that the performance of the signed regressor. LMS algorithm is superior than conventional LMS algorithm, the performance of signed LMS and sign- sign LMS based realizations are comparable to that of the LMS based filtering techniques in terms of Average Attenuation and computational complexity.